Behavior of Threading Dislocations from GaN Substrate to Epitaxial Layer. Issue 4 (9th April 2020) - Inotsume, Sho; Kokubo, Nobuhiko; Yamada, Hisashi; Onda, Shoichi; Kojima, Jun; Ohara, Junji; Harada, Shunta; Tagawa, Miho; Ujihara, Toru
Abstract : Threading dislocations (TDs) in the GaN homoepitaxial layer were nondestructively evaluated using X‐ray topography, Raman spectroscopy, and multi‐photon photoluminescence imaging. TDs in the GaN substrate have been identified as threading edge dislocations (TEDs), threading mixed dislocations (TMDs), and threading screw dislocations (TSDs). In article number 1900527, Hisashi Yamada and co‐workers discuss the direction and angle of inclined TDs in the GaN epitaxial layer. Stress relaxation via misfit dislocation is considered as a possible explanation for TED tilting toward the extra half plane.